The Impact of the Gig Economy on the Well-being of Independent Contractors. A Case Study of Uber, Bolt and Gokada - Egesi, Tochukwu (Graduate School of Business (GSB), 2023)
The gig economy is a rising global phenomenon in which gig workers provide “alternative work arrangements” for short-term contracts; also known as gigs, primarily agreed upon via digital platforms for various services such as food delivery or transportation. Work in the gig economy is typically on-demand, procured through an online platform, and delivered (and paid for) on a task-by-task basis. It is irregular, uncertain, unpredictable, contingent (i.e.feasible but not guaranteed), and impermanent. Independent contractors, freelancers, and self-employed are the most common terms used by platforms to describe gig economy workers. Consequently, it is vastly different from the traditional economy's demand-oriented, long-termed, and formal structure. Gig workers have access to relatively flexible, potentially self-sufficient labour. Still, they also face issues due to the nature of the work, its precariousness, and their interactions with platform businesses. The influence of the gig economy has primarily been studied using objective indicators such as micro-entrepreneurship, work-life balance, and autonomy. However, little research has been done on the gig economy's impact on workers' well-being in third-world countries such as Nigeria. This research will examine financial, mental, and physical elements of gig workers' well-being. The study aims to better understand the relationship between worker participation in the gig economy and their overall well-being and provide insight into workers' well-being within the Nigerian gig economy.